Development of weft-knitted and braided polypropylene stents for arterial implant - Fangueiro, Raúl (2010)
Textile biomedical materials have been used for various applications contributing considerably in improving quality of life. The current study aims at improving polypropylene fibre stents which may replace metallic ones. In order to produce the stents, weft-knitting and braiding technologies were used. In the braiding technique, by varying the takeup ratio (using gears with the appropriate number of teeth in the braiding machine), it was possible to manufacture regular braids with angles of 65 ° , 70 ° and 75 ° in order to obtain different covers. In the knitting technique, a circular machine was used and the tightness of the structure was adjusted by varying the loop length and thus the fabric loop density, resulting in variations of the sample diameter. The knitting machine had negative feed, and so loop length variations were achieved by varying the yarn input tension, the stitch cam settings and the fabric take-down tension. The samples were heat set. Yarns were contracted by setting at 130 ° C and 140 ° C, and this led to increasing the loop density and the flexural rigidity of the samples. A high cover of the samples resulted in a greater stiffness of the structures. The stents were evaluated by undertaking the tests required for arterial support: rigidity to radial compression, resistance to tensile forces and bending rigidity. The best results were obtained with braided structures. Future work may concentrate in improving the stent design and using new biocompatible fibres.